SAFETY COMMUNICATION EDUCATION IN IMPLEMENTING SAFE BEHAVIOR OF EMPLOYEES AT PLN OFFICE TANJUNG MORAWA, DELI SERDANG DISTRICT: SAFETY COMMUNICATION EDUCATION IN IMPLEMENTING SAFE BEHAVIOR OF EMPLOYEES AT PLN OFFICE TANJUNG MORAWA, DELI SERDANG DISTRICT - Irmayani, Irmayani; Ginting, Rosita; Bangun, Sri Melda; Samura, Jul Asdar (JURNAL PENGMAS KESTRA (JPK), 2022)
Safety communication is an interaction activity carried out by one worker with another worker so that the work carried out can run well and does not cause miscommunication which results in work accidents. Implementation of occupational safety and health communication aims to create safe behavior among workers. Prevention efforts that can reduce work accidents are by providing counseling about the application of safety communication. This PKM activity aims to educate employees about safe safety communication to workers. The method used in this activity includes counseling and discussion. This activity was carried out at the Tanjung Morawa PLN Office, Deli Serdang Regency. The targets for this activity were employees at the Tanjung Morawa PLN Office, Deli Serdang Regency, totaling 50 people. This activity was carried out in November 2022. The mechanism for implementing PKM activities is through several procedures which include: conducting a preliminary survey, arranging permits, coordination meetings, preparing facilities and infrastructure, preparing materials, preparing instruments, implementing activities and evaluating activities. From the results of the activities that have been carried out, it shows that the majority of participants have a working period of <5 years as much as 64%, the majority have high school education as much as 50%. There was an increase in knowledge about work safety communication before and after counseling by 38%. All participants in the activity took part in the activity enthusiastically. This PKM activity is expected to provide value to the community, especially workers at PT PLN Tanjung Morawa